Production performance & health of Lohmann Brown layer hens that received guanidinoacetic acid as a feed supplement - Jansen van Rensburg, Christine (University of Pretoria, 2023)
Dissertation (MSc Agric (Animal Nutrition)--University of Pretoria, 2022.